2012
DOI: 10.1111/j.1365-294x.2012.05531.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity enhances invasive ability of Spartina alterniflora

Abstract: Although genetic diversity is very important for alien species, which have to cope with new environments, little is known about the role that genetic diversity plays in their invasive success. In this study, we set up a manipulation experiment including three levels of genotypic diversity to test whether genotypic diversity can enhance the invasive ability of alien species, in our case the invasive Spartina alterniflora in China, and to infer the underlying mechanisms. There was no significant relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 40 publications
(89 reference statements)
3
37
1
Order By: Relevance
“…The fact that both trait and genotypic diversity were important for stem density and spatial spread in this experiment is consistent with prior findings that S. alterniflora intraspecific diversity can be important for density and spatial spread during the colonization stage (Wang et al . ). Abiotic stress from inundation and salinity is high in sparsely vegetated areas (Bertness ; Pennings & Bertness ), and these strong abiotic forces could have enhanced (c.f., Reusch et al .…”
Section: Discussionmentioning
confidence: 97%
“…The fact that both trait and genotypic diversity were important for stem density and spatial spread in this experiment is consistent with prior findings that S. alterniflora intraspecific diversity can be important for density and spatial spread during the colonization stage (Wang et al . ). Abiotic stress from inundation and salinity is high in sparsely vegetated areas (Bertness ; Pennings & Bertness ), and these strong abiotic forces could have enhanced (c.f., Reusch et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Wang et al . ) and across latitude (Seliskar et al . ; Salgado & Pennings ), has a genetic component and persists in a common garden.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, some studies point at the need to take within-species variation more explicitly into account for ecosystem functioning [4][6]. While, in recent years, studies on the role of genetic variation in biological invasions have shown that the maintenance of high genetic diversity is a feature of successful invasions [7][10], genetic diversity has rarely been experimentally addressed to explain invasiveness of species despite some evidence of both additive and non-additive effects of genetic diversity on colonization success [7], [11][13]. One recent example elucidating the role of genetic diversity for expanding species was provided by Crawford and Whitney [14], who could demonstrate positive effects of genetic diversity on attributes of colonization success of Arabidopsis thaliana , i.e.…”
Section: Introductionmentioning
confidence: 99%